2017
DOI: 10.3390/rs9101021
|View full text |Cite
|
Sign up to set email alerts
|

Structure-from-Motion Using Historical Aerial Images to Analyse Changes in Glacier Surface Elevation

Abstract: Abstract:The application of structure-from-motion (SfM) to generate digital terrain models (DTMs) derived from different image sources has strongly increased, the major reason for this being that processing is substantially easier with SfM than with conventional photogrammetry. To test the functionality in a demanding environment, we applied SfM and conventional photogrammetry to archival aerial images from Zmuttgletscher, a mountain glacier in Switzerland, for nine dates between 1946 and 2005 using the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 34 publications
3
62
0
2
Order By: Relevance
“…-1.32 my −1 between 1925 and 1953 and − 0.42 my −1 between 1953 and 1994, suggesting an increase in the glacier tongue thinning rates. Our values for the glacier tongue are also in line with the findings of Mölg and Bolch [52] who reported an average elevation change of −67 ± 5.3 my −1 for Zmuttgletscher (Swiss Alps), albeit for a larger area and a longer period, between 1946 and 2005.…”
Section: Discussionsupporting
confidence: 92%
“…-1.32 my −1 between 1925 and 1953 and − 0.42 my −1 between 1953 and 1994, suggesting an increase in the glacier tongue thinning rates. Our values for the glacier tongue are also in line with the findings of Mölg and Bolch [52] who reported an average elevation change of −67 ± 5.3 my −1 for Zmuttgletscher (Swiss Alps), albeit for a larger area and a longer period, between 1946 and 2005.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have found that errors in individual DEMs, both in the horizontal and vertical domain, propagate when calculating their difference, leading to inaccurate estima-tions of thickness and volume change (Berthier et al, 2007;Nuth and Kaab, 2011). In the present study, different approaches were adopted for georeferencing all the DEMs used in the analysis of the volume change of the Forni Glacier tongue (2007,2014,2016).…”
Section: Dem Co-registration For Glacier Thickness Change Estimationmentioning
confidence: 99%
“…In summary, although TLS point clouds are regarded as the most accurate (Naumann et al, 2013), they suffer from inhomogeneous point density and cumbersome logistics, and their potential in glacial environments is limited, unless a maximum uncertainty of 5-10 cm can be tolerated. Laser scanners are also employed on aerial platforms, including UAVs, where they can reconstruct terrain morphology with only slightly higher uncertainty than the terrestrial counterparts with a much greater coverage (Rayburg et al, 2009), but the high operational cost has limited the diffusion of this technique.…”
Section: Additional Remarksmentioning
confidence: 99%
“…The distance between the seven GCPs and the location of the same GCPs computed by the model [13] can be considered as an indicator of its internal coherence. In detail, Table 1 shows the two indicators MAE and RMSE.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike proprietary software, however, open source gives the possibility to examine [9,10], modify and redistribute the algorithms, and is particularly suitable for research reproducibility and replicability [11] and closer to the general concept of open science [12]. For this work, we have adopted MicMac, an open source photogrammetric software that implements SfM and and MVS algorithms [13]. …”
Section: Introductionmentioning
confidence: 99%